Serial dependence during visuomotor integration is robust to the passage of time and interference from intervening tasks. - Sirius, Esaú Ventura Pupo; Cravo, André Mascioli; de Azevedo Neto, Raymundo Machado (Memory & Cognition, 2026)
When intercepting a moving target, responses are systematically biased toward the time of impact from the previous trial. This phenomenon, known as serial dependence, relies on a memory mechanism that remains poorly understood. In interceptive tasks, multiple stimulus features—such as speed, time, or motor responses—can guide behavior on the current trial and may be stored to influence subsequent trials. Here, we examined how memory decays over short intertrial intervals (Experiment 1, N = 23) and whether interleaved tasks influence serial dependence (Experiment 2, N = 28). Participants performed either a temporal reproduction task or a speed judgment task, designed to compete for temporal and speed-processing resources, respectively. Our findings reveal that serial dependence persists across all intertrial durations and remains unaffected by intervening tasks. While serial dependence was neither reduced nor eliminated, variations in responses were partially influenced by prior temporal reproductions from the interfering task. These results suggest that serial dependence in visuomotor tasks is robust to both the passage of time and external interference, though task responses may be subtly modulated by preceding temporal reproductions.